Design Analysis of a Chain Conveyor Grid Feeder Using Finite Element Analysis and Performance Testing for Non Value Added Reduction: A Battery Industry Case Study - Timotius Anggit Kristiawan; Rosyadul Muzzaqi; Farika Tono Putri; Mochammad Ariyanto (International Journal of Innovation in Mechanical Engineering and Advanced Materials, 2026)
Non-Value-Added (NVA) waiting time was identified in PT XYZ’s Grid Feeding Process due to the limited filling capacity of the paster machine’s input conveyor. This study designs and evaluates the structural feasibility of a chain-conveyor grid feeder to support line balancing, enable sustained NVA reduction, and evaluate the operational impact of implementation. Method include CAD design, structural verification via finite element analysis cross-validated between ANSYS Workbench and SolidWorks Simulation for two subsystems (frame and conveyor), fabrication and on-floor installation, and a before–after time study. ASTM A36 is used as the primary material, and a linear static analysis is performed under the heaviest-load (fully filled) scenario. The FEA result shows maximum von Mises stresses of 55–57 MPa (frame) and 60–76 MPa (conveyor), all below the A36 yield strength (250 MPa), with maximum deflection of 0.41–1.09 mm and a minimum safety factor of 2.3–4.54. After implementation, NVA (waiting) in the grid feeding process was eliminated and staffing across two lines decreased from two operators to one. These findings indicate that the proposed chain-conveyor grid feeder is structurally safe under the heaviest load and effectively improves grid-feeding efficiency.